Ալեքսանդր Մեծի դամբարանի և աճյունի տեղորոշումը. նոր եզրահանգումներ - Քրիստիան Թյություջյան դը Վարդավան (ՀՀ ԳԱԱ հրատ.)
Исследовании, проведенные в мае 1996 г. в гробнице мечети Неби Даниэл в Александрии (Египет), позволяют утверждать, что раскопки в той же мечети и ее окрестностях Эваристо Бречиа (1928 г.) отнюдь не опровергают ни мнения Зогреба и Тусуна о том, что в этой гробнице находятся также останки Александра Великого, ни того, что эта мечеть построена вертикально к Соме.Examination in May 1996 of the crypt of mosque Nebi Daniel in Alexandria (Egypt)enables the author to demonstrate that excavations led in 1928 by Evaristo Breccia in and around the same mosque do not refute in any way Zogheb's and Toussoun's theory that Daniel's grave contains the remains of Alexander the Great, neither that this mosque is indeed built immediately over the Soma.
Keywords: Auxiliary Sciences of History; CC Archaeology; N Fine Arts; NA Architecture